BPA and low-Se exacerbate apoptosis and mitophagy in chicken pancreatic cells by regulating the PTEN/PI3K/AKT/mTOR pathway - Wenying Sun; Yutian Lei; Zhihui Jiang; Kun Wang; Huanyi Liu; Tong Xu (Journal of Advanced Research)
Introduction: Bisphenol A (BPA) is a widespread environmental pollutant which has serious toxic effects on organisms. One of the crucial trace elements is selenium (Se), whose shortage can harm biological tissues and enhance the toxicity of contaminants, in which apoptosis and autophagy are core events. Objectives: An in vivo model was established to investigate the effects of BPA and low-Se on chicken pancreatic tissue, and identify the possible potential molecular mechanism. Methods: A total of 80 1-day-old broiler chickens (Xinghua Chicken Farm, Harbin, China) were stochastically divided into 4 groups (n = 20/group): Control group, BPA group, low-Se group, and low-Se + BPA group. Pancreatic tissue was collected at day 42 to detect changes in markers. Results: First, the data showed that BPA and low-Se exposure gave rose to structural abnormalities in pancreatic tissue, oxidative stress, mitochondrial dysfunction and homeostasis imbalance, apoptosis and mitophagy. In addition, the co-exposure of BPA and low-Se caused the most serious damage to pancreatic tissue. In terms of mechanism, it was found that apoptosis and mitophagy induced by BPA and low-Se were related to the activation of PTEN/PI3K/AKT/mTOR pathway. Conclusion: In summary, the study found that BPA and low-Se exacerbated mitochondria damage, apoptosis and mitophagy by regulating the PTEN/PI3K/AKT/mTOR pathway.